Trabecular bone: texture analysis in CT to improve osteoporosis diagnosis in Duchenne muscle distrophy patients. - Castellanos Abrego, Norma Pilar; Martínez Coria, Elisa; Gutierrez Martínez, Josefina (Revista Mexicana de Ingeniería Biomédica)
In recent years, interest in bone mineral densitometry (BMD) for children has increased, mainly due to the varieties of disease that influence bone growth. Trabecular bone densitometry in CT from lumbar vertebra is usually used clinically as a good indicator of bone deterioration and fracture risk. Nevertheless, diagnosing osteoporosis in obese and Duchenne Muscle Distrophy (DMD) children by BMD has been difficult due to the attenuation of radiation dose by abdominal fat, which could lead to overestimation of the degree of bone deterioration. The present work is an effort to improve pediatric osteoporosis diagnostic efficacy by analyzing the trabecular bone texture via CT with two frequency based methods: fractal dimension with power spectrum (D) and wavelet packets (WP). Healthy young adults group in the peak bone mass was statistically compared (t-student) with osteoporotic women with either fractal dimension or the four WP energy bands, and the results suggested significant differences. Applying ANOVA to three DMD children groups classified by their z-score as having normal, low and very low bone mineral density, significant differences were also found. At last, when comparing the DMD pediatric groups with that osteoporotic women, great statistical significance was found for all texture indicators. Results shown that the introduced techniques for image texture analysis could quantify the trabecular bone deterioration; this may help to improve the osteoporosis diagnosis in overweight patients, in specific DMD children, where it is often a diagnostic challenge.